Princess in the spotlight - Cabot, Meg (New York HarperCollins, 2001)
Having recently discovered she is the sole heir to the throne of a tiny European principality, fourteen-year-old Manhattan resident Mia writes in her journal about her attempts to cope with this news, as well as with more typical teenage concerns
1
NEW, LITERATURE
Keywords: Diaries -- Fiction; Identity -- Fiction; Princesses -- Fiction; Schools -- Fiction; New York (N.Y.) -- Fiction